New Media: Twitter Netizen Criticism Of The LGBT Coldplay Campaign In Indonesia - Nuraini, Nuraini; Sazali, Hasan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This This article seeks to analyze Twitter users' criticism of the Coldplay concert, which purportedly will spark an LGBT campaign. This elucidated a range of responses from the general public , from those who felt normal to those who felt dread. The advantages and disadvantages of the Coldplay concert and the LGBT campaign raised an issue that is still in public consciousness. This article employs a qualitative methodology with a sociological perspective. This article's primary data is collected tweets from individuals, while the secondary data is derived from scientific works pertinent to the topic under discussion. The results of the discussion indicate that Twitter users are indeed dynamic. However, this issue was downplayed due to the assumption that people don't care about the LGBT campaign and only want to watch Coldplay perform. Unfortunately, this topic has begun to be discussed on a national scale, eliciting a variety of negative responses. The government must adopt a qualified initiative, which at this level is an agreement note, to prevent Coldplay from disseminating LGBT messages in Indonesia, which could cause chaos.